Elevated Fluoride Products Enhance Remineralization of Advanced Enamel Lesions - ten Cate, J.M.; Buijs, M.J.; Miller, C. Chaussain; Exterkate, R.A.M. (Journal of dental research, 2008)
Caries prevention might benefit from the use of toothpastes containing over 1500 ppm F. With few clinical studies available, the aim of this pH-cycling study was to investigate the dose response between 0 and 5000 ppm F of de- and remineralization of advanced (> 150 μm) enamel lesions. Treatments included sodium and amine fluoride, and a fluoride-free control. Mineral uptake and loss were assessed from solution calcium changes and microradiographs. Treatments with 5000 ppm F both significantly enhanced remineralization and inhibited demineralization when compared with treatments with 1500 ppm F. Slight differences in favor of amine fluoride over sodium fluoride were observed. The ratio of de- over remineralization rates decreased from 13.8 to 2.1 in the range 0 to 5000 ppm F. As much as 71 (6)% of the remineralized mineral was calculated to be resistant to dissolution during subsequent demineralization periods. With 5000-ppm-F treatments, more demineralizing episodes per day (10 vs. 2 for placebo) would still be repaired by remineralization.